METHODS OF TEACHING GRAMMAR TO ELEMENTARY STUDENTS (Ustozlar uchun, 2026)
Teaching grammar to elementary students is an essential part of language learning because it helps learners communicate accurately and confidently. Young learners usually understand grammar better when it is presented through games, visual materials, songs, and interactive activities instead of traditional memorization. The purpose of this article is to analyze effective methods of teaching grammar to elementary school students and identify approaches that improve students’ motivation and understanding. The study is based on qualitative analysis of pedagogical literature and classroom practices. The results show that communicative and activity-based approaches increase students’ participation and make grammar learning more meaningful. The article concludes that grammar instruction for young learners should be practical, engaging, and connected with real-life communication.